Utility consumption among Malaysian electricity users in government buildings - Baharun, Rohaizat (Institute of Electrical and Electronics Engineers Inc., 2014)
In this study, pattern of electricity consumption for institutions and at workplaces in Malaysia studied. The main purpose of this study is to investigate the utility consumption among Malaysian electricity users. This study is designed to find out the different attitude and awareness toward energy consumption among staffs and students and also to identify respondents' environmental concern ranking. The sample size of this study are staffs (teaching and administrative) and students of Faculty of Engineering in one of the Malaysian university situated at south of Peninsular Malaysia, and the evaluation based on the suggested framework. The significant different were found when researcher multiple awareness with micro and macro environment concern. Self-efficacy is the highest ranking in environmental concern rated by the respondent. Energy consumption has the significant effect towards environmental concern attitude and energy consumption is mediated by the environmental concern.